IMPROVING CONCEPT UNDERSTANDING OF NATURAL AND SOCIAL SCIENCE MATERIALS THROUGH PROJECT-BASED LEARNING IN ELEMENTARY SCHOOLS - Leli Lestari; Novi Indah Puspita Sari (Universitas Islam Negeri Mataram, 2023)
This study aims to determine how the application of project-based learning and its results in improving the understanding of the concept of IPAS material in grade IV students at the Elementary school of Bunder 1 Pademawu, Pamekasan. This type of research uses the Mc. Taggart's model uses 4 stages. The research was carried out using 2 cycles and carried out as many as 2 meetings in each cycle. Data collection using observation techniques consisting of observation of teacher activities, student activities, and tests. The results of the research conducted on tests carried out by students resulted in scores at the pre-cycle stage of students who had a complete score of 16.60% with an average of 41.97, in cycle 1 students who were complete by 50% with an average of 62.25 and in cycle 2 students who had a complete score of 75% with an average of 74.83. Meanwhile, when viewed from the observation of teacher activities by teachers in cycle 1 and cycle 2, namely 82.5%: 90%. In the observation of student activities by students in cycle 1 and cycle 2, namely 81.87%: 83,95%. In the observation of student activities by the teacher in cycle 1 and cycle 2, namely 81.67%: 85%. So it can be said that project-based learning can improve the understanding of the concept of IPAS. The better the application, the more understanding gained by students will increase